THE ANALYSIS OF TRANSITION IN BBC DESTINATION’S NEWS ARTICLES - Prameswari, Intan; Sopha, Diana (Fakultas Sastra UMN AL Washliyah, 2025)
English is a global language widely used for communication in various fields, including education, business, and media. In written texts, particularly in news article, the structure and clarity of language are critical in conveying information effectively to diverse audiences. In writing an article needs transitions which help the ideas of the text flow logically and cohesively, and create a smoother, clearer, more cohesive piece of writing from sentence to sentence. Transitions are bridges between what has been read and what is about to be read. Transitions help readers move from sentence to sentence. Understanding these transitions is crucial for comprehending the current state of news articles. Transition theory used in this research is based on Diana hacker (2002). Transitions in this research news’s article based on BBC Destination’s news. News’s articles in this research limited to 6 news articles. The titles are: An eerie portal to the Maya underworld, Australia's X-rated underwater show, India's 10,000 forgotten mansions, The five best things to do in Boston's Seaport District, Saudi’s lineage of interior stylists and What did Stonehenge sound like?.